"Whiskered", Saman [sic] Tree, Trinidad - (:unkn) unknown (F.P.Bruce-Austin, 2010)
A view of a Samaan Tree covered with plant parasites.
Colour: Sepia: Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Trees--Samaan; Parasitic plants